Addressing the gas emission problem of the world's largest coal producer and consumer: Lessons from the Sihe Coalfield, China. (November 2020) - Wang, Wei; Li, Hong; Liu, Yanwei; Liu, Mingju; Wang, Haifeng; Li, Wei
Abstract: Exploitation of deep-lying coal resources, an inevitable result of the conflict between the depletion of shallow coal resources and the enormous demand for energy, is subject to safety accidents caused by increased risks of coal and gas outbursts. Factors such as low gas extraction efficiency resulted from poor air permeability of coal seams, failure of extracting methane in coal mine and low utilization rate of the methane extracted from coal mine not only cause serious greenhouse effect, but also waste a lot of energy and fuel. Recent innovations have seen that the new elements of three zone linkage based on the joint mining of coal and gas is used to ensure the safety of workers and achieve the maximum energy comprehensive utilization. Sihe coalfield represents a particularly challenging mining environment for applying this practice. Due to the high risk of coal seam outburst, mining disturbance will not only cause coal and gas outburst and cause casualties, gas emissions will also cause serious greenhouse effect and energy waste. Sihe coalfield has formed a green coal mining mode of low-carbon and environmental protection, which provides attractive experience and lessons for the application of other coal mines at home and abroad. This approach achieves multiple benefits: large-scale extraction and utilization of CBM resources, safe and efficient production of coal areas, and reduction in greenhouse methane emissions. The successful application of this method to Sihe coalfield provides a new way of gas management for other coal mines with similar geological conditions. In view of the extreme nature of Sihe minefield, it will be easier to implement in other coal mines. Graphical abstract: Highlights: A new method of green gas drainage and utilization is put forward. Analyzed the feasibility of protective layer technology. The NPV method was used to compare the comprehensive benefits of PLM and TZLGEU. The advantages of coal and coalbed methane co mining in Sihe coal mine are given.